What makes rural, traditional, cultures more sustainable? Implications from conservation efforts in mountainous rural communities of Japan. (16th November 2016) - Tani, Yuichiro; Hashimoto, Shizuka; Ochiai, Mototsugu
Abstract: Culture has long been considered one of the key elements characterising rurality and plays a central role in rural development. While the majority of research on cultural sustainability focuses on specific resources such as heritage or arts, few studies exist on the culture of rural production and life. Focusing on rural villages of Northeastern Japan, this study explores the key to conserving traditional, rural Japanese cultures—including slash-and-burn agriculture, using ash in cooking, and weaving cloth from plant fibres—by examining its spatial, gender, and generational variations, with semi-structured interviews and a questionnaire survey. Our analysis clarified that these regional cultures have a varied pattern of regional distribution, associated with various factors such as methods and habits of cultural practice, the state of related industries, and commodification of culture. Furthermore, in response to such factors, the cultures showed gender and generational variations of practice, with the former influenced by the segregation of roles, particularly with regard to household labour. Most cultural practices appear to be undertaken by those of advanced years, so encouraging the maintenance of this culture among the younger generation through conservation organisations is vital to revitalising its economic significance. When examining the maintenance of a culture in a particular region, it is valuable to first understand the regional, gender, and generational differences in cultural practice for the various elements from which the overall culture can be distilled.